Totally submuscular implantation of subcutaneous implantable cardioverter defibrillator: a safe and effective solution for obese or oversized patients. Issue 10 (17th September 2016) - Droghetti, Andrea; Locatelli, Alessandro; Casiraghi, Bruno; Malacrida, Maurizio; Arupi, Michele; Ragusa, Mark
Key Clinical Message: The subcutaneous implantable cardioverter–defibrillator (S‐ICD) is a safe alternative to transvenous ICD. We describe a submuscular S‐ICD placement technique in a severely obese with an oversized chest. Submuscular configuration allows optimal system positioning and impendence values warranting a safe and effective shock transmission. This technique is safe and improves patients comfort. Abstract : The subcutaneous implantable cardioverter–defibrillator (S‐ICD) is a safe alternative to transvenous ICD. We describe a submuscular S‐ICD placement technique in a severely obese with an oversized chest. Submuscular configuration allows optimal system positioning and impendence values warranting a safe and effective shock transmission. This technique is safe and improves patients comfort.